Job Market Test Attendance System With Health Protocols Using The Internet Of Things - Putra, Andriyan Dwi; Hakim, Lukman; Mustopa, Ali (Sistemasi: Jurnal Sistem Informasi, 2023)
During the transitional period related to the coronavirus outbreak, the need for jobs began to increase. The number of prospective workers who will apply for a job in a company by doing a selection test at the Job Exchange. On the other hand, to suppress the spread of this epidemic, the interaction between Job Exchange officers and prospective job applicants must be limited. So by creating a Job Exchange Test attendance system according to health protocols with the Internet of Things devices, it can be used to limit the interaction of prospective job applicants with job exchange officers. This system was built using the Waterfall Model Software Development Life Cycle method, by utilizing the ESP8266 microcontroller components, the MFRC522 module, and the MLX90614 sensor which will support the performance of this system. The results of this study are taboos for prospective job applicants who have an illegal condition or have a temperature above normal, may not enter the room without interacting directly with the officer, but the device will sound a buzzer notification and a warning message will be sent from the microcontroller and received by the officer via telegram. In this study, a comparison was made to obtain the ideal distance for scanning body temperature at various different distances, and the results of the comparison obtained the smallest percentage error value of 0.027% at a distance of 3 cm.